Chemical and Toxicological Analysis of Antiretroviral Drugs - T. N. Komarov; M. V. Belova; D. D. Stolyarova; I. E. Shohin; D. S. Bogdanova; O. A. Miskiv; Yu. V. Medvedev; I. M. Korenskaya (Разработка и регистрация лекарственных средств, 2019)
Introduction. Human Immunodeficiency Virus (HIV) is one of the main socially significant infection all over the world. HIV-positive patients take medical care, including antiretroviral drugs (ARVs) pharmacotherapy. Like all drugs, ARVs have lots of side effects that should be taken when prescribing drugs as part of highly active antiretroviral therapy. There are many cases when side effects of ARVs caused patients to enter the toxicology department. Therefore, the development of new methods for the analysis of ARV in biological fluids for the timely diagnosis of treatment of poisoning of this group of drugs is relevant today.Aim. The aim of this study is development of screening analysis of atazanavir, abacavir, nevirapine, ritonavir, lopinavir, zidovudine, darunavir and efavirenz in the urine to identify these drugs as possible toxicants for poisoning by high-performance liquid chromatography with tandem massselective detection (HPLC-MS/MS).Materials and methods. Identification of ARV was performed by HPLC-MS/MS. Methanol precipitation method was used as a sample preparation.Results and discussion. The optimal conditions for sample preparation, chromatographic separation, and mass-spectrometric detection were selected to determine the studied ARVs. This method was tested on urine samples from patients in the Department of Acute Poisoning and Somatopsychiatric Disorders (OOSPD) with acute ARV poisoning.Conclusion. This screening method for analyse atazanavir, abacavir, nevirapine, ritonavir, lopinavir, zidovudine, darunavir and efavirenz in human urine has been developed by HPLC-MS/MS. The developed method can be used to identify these drugs as possible toxicants in case of poisoning. The prospect for the development of the topic is the inclusion of new molecules in the method and quantitative determination of the studied ARVs.